2012
DOI: 10.1029/2011gl050709
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emissions from Indian monsoonal estuaries

Abstract: Estuaries are known to be strong source for atmospheric CO2, however, little information is available from Indian estuaries. In order to quantify CO2 emissions from the Indian estuaries, samples were collected at 27 estuaries all along the Indian coast during discharge (wet) period. The emissions of CO2 to the atmosphere from Indian estuaries were 4–5 times higher during wet than dry period. The pCO2 ranged between ∼300 and 18492 μatm which are within the range of world estuaries. The mean pCO2 and particulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 34 publications
6
72
4
Order By: Relevance
“…On the other hand, lower mean values of pH were found in the west coast estuaries (6.8290.52) than the east coast estuaries (7.6590.57), suggesting that further higher nutrients in the former are caused by higher rates of organic matter decomposition and it is consistent with DO saturation. Recently Sarma et al (2012) found higher pCO 2 levels in the Indian estuaries, which were attributed to organic matter decomposition. Nevertheless, the annual mean N 2 O saturation in the Indian estuaries (2049137%) was significantly less than the European (465%; Bange, 2006 and271% Barnes andUpstill-Goddard, 2011) and the American estuaries (165Á618% ; Table S1; supplementary information).…”
Section: Spatial and Temporal Variations In N 2 O Concentrations In Tmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, lower mean values of pH were found in the west coast estuaries (6.8290.52) than the east coast estuaries (7.6590.57), suggesting that further higher nutrients in the former are caused by higher rates of organic matter decomposition and it is consistent with DO saturation. Recently Sarma et al (2012) found higher pCO 2 levels in the Indian estuaries, which were attributed to organic matter decomposition. Nevertheless, the annual mean N 2 O saturation in the Indian estuaries (2049137%) was significantly less than the European (465%; Bange, 2006 and271% Barnes andUpstill-Goddard, 2011) and the American estuaries (165Á618% ; Table S1; supplementary information).…”
Section: Spatial and Temporal Variations In N 2 O Concentrations In Tmentioning
confidence: 95%
“…Hence, the biogeochemical processes in monsoonal estuaries during discharge period could be completely different from that of a dry period. Recently, Sarma et al (2012) estimated emissions of CO 2 from the Indian estuaries as Â2 )10 12 gC to the atmosphere annually, which is about 10 times less compared to European estuaries. Such low CO 2 fluxes from the Indian estuaries result from high flushing rates and less dense human settlements along the banks of estuaries.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated carbon release to the atmosphere from Indian (inner) estuaries (1.9 Tg C yr −1 ; Sarma et al, 2012) is relatively small compared to the total river flux of South Asia region. The monsoonal discharge through these estuaries have a short residence time of OC, which helps the OC matters to be transported relatively unprocessed to the open/deeper ocean.…”
Section: Riverine Carbon Fluxmentioning
confidence: 97%
“…Since then, CO 2 data coverage has tremendously increased with additional studies at subtropical and tropical latitudes (for example Sarma et al, 2012;Chen et al, 2012;Rao and Sarma, 2016) and in the large river-estuarine systems such as the Amazon (Lefèvre et al, 2017), the Mississippi , the Yangtze (Changjiang) (Zhai et al, 2007;Zhang et al, 2008), and the Pearl (Guo et al, 2009;Zhou et al, 2009). The number of studies on CH 4 in estuarine and coastal environments has not increased in recent years as spectacularly as those concerning CO 2 , attracting less research efforts because the marine source of CH 4 to the atmosphere (0.4-1.8 TgCH 4 yr −1 ; Bates et al, 1996;Rhee et al, 2009) is very modest compared to other natural and anthropogenic CH 4 emissions (Kirschke et al, 2013); however, continental shelves and estuaries are more intense sources of CH 4 to the atmosphere than the open ocean, in particular shallow and permanently well-mixed coastal zones (Borges et al, 2016.…”
Section: Introductionmentioning
confidence: 99%